Lords of the Lakes, Akwesasne Mohawks, and Turbulent Scots - Campbell, Alexander (Ontario History, 2024)
The Nutfield Tract, also known as the Glengarry Reservation, or the Indian Lands, was a large domain set aside on the northern banks of the St. Lawrence River for use by the Akwesasne Mohawks in 1784. This article explores how its later monetization weakened that Native mission’s internal cohesion especially after the North West Company’s head, William McGillivray, tried to acquire the Glengarry Reservation between 1809 and 1821. Disquiet within the St. Regis community likewise became evident amongst their Loyalist and Gaelic-speaking tenantry who grew concerned about the security of their property and lack of enfranchisement. The Nutfield Tract imbroglio, after decades of twists and turns, was finally resolved by the 1844 Bagot Commission which recommended that the Crown’s recovery of the Indian Lands and its subsequent disposal to registered lessees would best protect the interests of all those concerned.